2016
DOI: 10.1111/vsu.12552
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy for Removal of Unilateral Noninvasive Pheochromocytomas in 10 Dogs

Abstract: With careful case selection, laparoscopic adrenalectomy for resection of pheochromocytoma was feasible and could be performed efficiently by experienced laparoscopic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
(143 reference statements)
1
17
0
Order By: Relevance
“…The failure to mitigate hypertensive episodes with phenoxybenzamine pre-treatment was also demonstrated in several subsequent case series. 7,35,36 Breakthrough hypertension can still occur due to incomplete blockade with phenoxybenzamine and via release of other vasoconstrictive mediators such as neuropeptide Y. 37 To treat an intra-operative hypertensive crisis, the inhalational anaesthetic agent can be increased or acepromazine can be administered.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to mitigate hypertensive episodes with phenoxybenzamine pre-treatment was also demonstrated in several subsequent case series. 7,35,36 Breakthrough hypertension can still occur due to incomplete blockade with phenoxybenzamine and via release of other vasoconstrictive mediators such as neuropeptide Y. 37 To treat an intra-operative hypertensive crisis, the inhalational anaesthetic agent can be increased or acepromazine can be administered.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic adrenalectomy has gained in popularity in veterinary medicine and observational studies have shown that it results in more rapid recovery, shorter hospitalization, fewer wound complications and shorter surgical time than open laparotomy , . The size of the PCC and the extent of vascular invasion are the most important criteria in choosing between laparoscopy and open laparotomy.…”
Section: Treatmentmentioning
confidence: 99%
“…Classification of studies by organ system is presented in Tables S1 and S2. Numbers of studies and participants were reported within each organ/system group including female genital tract (22 studies [n = 1407 dogs]), 1,7,11,20,30‐47 urinary tract (7 studies [n = 114]), 3,48‐53 stomach (9 studies [n = 250]), 10,18,54‐59 intestinal tract (5 studies [n = 48]), 60‐64 liver (5 studies [n = 288]), 12,17,65‐67 adrenal gland (5 studies [n = 62]), 13,28,68‐70 spleen (7 studies [n = 111]), 19,71‐76 and other (4 studies that included gastropexy and ovariectomy procedures [n = 148]) 9,77‐79 . One experimental study, in which colopexy in seven male dogs was described, was classified as intestinal tract even though these dogs were also sterilized during the surgical procedure because this study reported only complications and outcomes related to colopexy 63 .…”
Section: Resultsmentioning
confidence: 99%